The crucial role of platelet stacking mode in strength and toughness of nacre - S.M. Liang; H.M. Ji; X.W. Li (Materials & Design, 2023)
Nacre can be classified as columnar or sheet nacre based on the stacking mode of platelets, which is respectively featured by an aligned or staggered platelet arrangement. To determine the more suitable type for biomimetic modeling, the inherent structure–property relationships of both nacres were explored via mechanical tests with theoretical and numerical analyses. It is found that sheet nacre exhibits an outstanding combination of high strength and high toughness compared to columnar nacre under both tensile and compressive stresses, attributing to its staggered stacking characteristic. Under tensile stress, its effect can be quantitatively characterized by the platelet overlap ratio, with a measurement of 0.11 for columnar nacre and 0.47 for sheet nacre, where the larger ratio contributes to a higher tensile strength. Analytical and numerical models reveal that a higher overlap ratio or staggered stacking can trigger the transition from chain-like to step-like failure modes, significantly contributing to improved toughness. Under compressive stress, compared with columnar nacre’s aligned stacking, sheet nacre’s staggered platelet arrangement effectively postpones kinking failure and enhances both compressive strength and toughness. Therefore, the staggered arrangement of platelets in sheet nacre produces the more balanced mechanical properties, offering beneficial references for designing high-performance nacre-inspired materials.